Persepsi Masyarakat Terhadap Pelaksanaan Pembangunan Kota Kotamobagu - Gugule, Hamdi; Mesra, Romi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
In the implementation of the development that has been going on for 3 (three) years, the leadership of the first elected Mayor/Deputy Mayor of the people, feels the need to do a study of people's perceptions in seeing the implementation of development, both physical development and non-physical development. (planning aspect). The purpose of carrying out this activity is to find out how the public perception of the implementation of development in Kotamobagu City. The data collection techniques are in the form of pre-surveys, field observations, interviews, and questionnaires. The results of the study are the characteristics of respondents, responses to development changes (progress), prominent development classifications, development programs that need to be developed in the future, development of regional economic growth centers and development of modern markets, and order and arrangement of beautiful and green cities